AN EMPIRICAL ASSESSMENT OF MONTHLY DEFAULT PENALTIES AS A DETERRENT MEASURE OF DEFAULT ON HIGHEREDUCATION LOAN RECOVERY IN KENYA - Machogu, Clifford; Shisia, Adam; Nzioki, Paul Muoki; Kiplimo, Sirma (International Journal of Economics, Commerce and Management, 2017)
Despite the various measures taken by Higher Education Loans Board (HELB) in Kenya to increase its loans recovery, there has been reluctancy by HELB funded University graduates to repay their loans. In this regard, HELB has put in place several measures with a view to boost its recovery. Of particular interest to the present study is the monthly penalty of Ksh.5000 with effect from 2010 which acts as a deterrent measure to would be defaulters. The aim of this study was therefore to assess the deterrent effect of monthly default penalty on higher education loan recovery in Kenya. The study used both descriptive design and longitudinal design. Both primary data and secondary data were collected from all those undergraduate students who benefitted in any Kenyan university. Descriptive analysis involved means and standard deviations as measures of central tendencies and dispersion respectively. Inferential statistics limited itself to regression and correlation analysis. The study found out that there is a significant association between monthly default penalty and loan recovery. It also found that monthly default penalty on defaulters was a significant deterrent of HELB loan defaulters. The study recommends the establishment of a default management program as an extra step to reducing default rate and ensuring that loanees are aware of their responsibility. It also recommended that future studies should explore factors that cause loan defaulting.
Keywords: Deterrent measures; Monthly Default Penalty; Loan Recovery; Higher Education Loans Board; Kenya